FUNCTIONS OF DRUG ADDICTS’ JARGON AND WORD-BUILDING MEANS OF THEIR IMPLEMENTATION (A CASE STUDY OF SOCIOLINGUISTIC QUESTIONNAIRES AND JARGON DICTIONARIES) - T. V. Artemova; P. A. Katyshev; S. V. Olenev; Yu. S. Pauli; S. K. Sokolova (Вестник Кемеровского государственного университета, 2014)
The article reveals the role of word-building in the performance of such drug addicts’ jargon functions as nominative, utilitarian, worldview, pseudo-aesthetic, playing, agitational, symbolic, identificatory, and conspiratorial. Based on the material of vocabulary gathered during the regional sociolinguistic studies, as well as in the analysis of dictionaries of drug addicts’ jargon, the word-building means of implementing the named functions are studied; the issue of natural causes of drug addicts’ jargon "conspiracy" is discussed. It is concluded that drug addicts' jargon is not a primitive subsystem of their language, and its negative assessment by scientists is often caused by the negative attitude to the phenomenon of drug addiction.